Application of Queuing Theory in Analyzing the Use of Production Capacity - Marsudi, Muhammad (International Journal of Integrated Engineering, 2010)
Queuing theory is a major topic of applied mathematics that deals with phenomenon of waiting and arises from the use of powerful mathematical analysis to describe production processes. This study examines the use of production capacity of facilities in Fujitsu Components (M) Sdn. Bhd. based on queuing theory. The aim of this study is to achieve an appropriate queuing analytical model and determine its performance measures by analyzing the capacity requirements and estimating manufacturing cycle times. Field study has been conducted in several production departments in Fujitsu Components (M) and production data has been collected through selftiming, past collected data and recorded data approach. The production processes has been simplified into seven independent series of stations, which are Stamping, Riveting, Cutting, Bending, Packing and two Inspection stations. The capacity requirement has been determined by utilization factor where the benchmark equal to one. This study then represents the data in form of queuing analytical model to analyze the performance measures. The queuing analytical model later identified that all stations having enough capacity (uj